Hypofractionated intensity-modulated radiation therapy with concurrent cisplatin in locally advanced oropharyngeal cancer: feasibility experience from a Government cancer centre of Eastern India in a resource-constrained setting. Issue 1 (29th May 2019) - Rangineni, Srikrishnadevarayulu; Lahiri, Debarshi; Misra, Biplab; Maji, Tapas; Roy, Sanjoy; Ray, Dilip Kumar; Banerjee, Saptarshi; Das, Subhadip; Pallath, Ashwin Mohandas
Abstract: Purpose: Radiation therapy (RT), in combination with chemotherapy, is the mainstay in the treatment for locally advanced oropharyngeal cancer. We analysed the tumour response and the toxicity profiles in patients having locally advanced oropharyngeal cancers receiving hypofractionated intensity-modulated radiation therapy (IMRT) and concurrent chemotherapy with Cisplatin investigating the feasibility and radiobiological efficacy of the regimen, along with its use as a resource-sparing alternative for a high-volume centre. Material and Methods: The records of 41 eligible patients with locally advanced squamous cell carcinoma of oropharynx, registered from September 2015 to April 2017, treated with hypofractionated IMRT with concurrent Cisplatin, were analysed from the hospital database. Patients received concurrent chemo-radiation with 2 cycles of 3-weekly cisplatin on day 1 and day 22 along with hypofractionated IMRT, 55 Gy delivered in 20 fractions over 4 weeks. Patients were observed for any radiation reaction or chemotherapy toxicity at least once a week during the course of radiation therapy. Results: Twenty-nine patients (70·7%) achieved complete response and remaining 12 showed partial response. Acute grade 3 toxicity was observed mostly in the form of oral mucositis and radiation dermatitis. Both grade 3 oral mucositis and radiation dermatitis were seen in 15 patients (36·6%) and 7 patients (17%), respectively. The most common late toxicities were dysphagia and dry mouth. Twenty-five patients (61%) completed the overall treatment within 4 weeks' duration. Conclusion: This hypofractionated regimen is feasible and was associated with tolerable acute and late morbidity and satisfactory locoregional response. Larger prospective, multi- institutional studies examining similar schedules may be undertaken to establish this as a standard practice, particularly for a high-volume centre.